Surviving the Post Silicon Valley Bank Crisis - Beainy, Dr. Richard Hanna; Kamel, Dr. Jeanne Kaspard (International Journal of Membrane Science and Technology, 2023)
In the wake of the sudden collapse of three major financial institutions in the United States (Silicon Valley Bank, Silver Gate, and Signature Bank) the Federal Government intervention was swift and quick and even surpassed regulations by promising a full refund for all bank depositors, yet was the major intervention by the Government and the United States President Joe Biden a sign of strength or weakness? This study analyzes the importance of the financial sector to achieve economic prosperity as well as the readiness of the United States Government to face future challenges that might jeopardize the entire international financial system through alarming World Bank Data.